The Spanish Language at UNWE (Methodological and Academic Production to Meet Training Goals) - Ishpekova–Bratanova, Kalina Filipova (Research Papers, 2021)
The article presents all textbooks, teaching aids and monographs related to Spanish language teaching at UNWE. The specificity and structure of each publication, the adequacy in view of the objectives of education, its effectiveness for the high-quality preparation of prospective students and students are considered, paying attention to compliance with the dynamically changing university and world requirements in the field of foreign language teaching and the trend towards diversification and renewal of academic production.
Keywords: Foreign language teaching at UNWE; Textbooks in Spanish as first and second foreign language; Teaching aids for specialized training